The effect of PDMS on Ti6Al4V for surface anti-wear and corrosion resistance - Mohd Harizan, Zul; Ramdziah, Md Nasir; Mahadzir, Ishak@Muhammad; Moinuddin Mohammed, Quazi (Malaysian Tribology Society (MYTRIBOS), 2024)
This paper explores the effectiveness of Polydimethylsiloxane (PDMS) coating combined with laser texturing on Ti6Al4V surfaces to enhance wear and corrosion resistance for various industrial applications. The methodology involves initially applying PDMS coating on the sample surface, followed by laser texturing (PDMS-LT) to achieve superhydrophobic surface wetting behavior. The samples are subjected to wear sliding tests under dry, artificial seawater, and engine oil environments at a load of 10N and a speed of 75 m/min for 30 minutes, alongside corrosion potentiodynamic tests conducted in artificial seawater conditions. The results indicate a substantial improvement in wear resistance, specifically, the PDMS-LT demonstrated a notable 29.41% enhancement in wear resistance compared to untreated Ti6Al4V, exhibiting a wear rate of 3.45 x 10-3 mm3/m.N. Moreover, under oil lubrication conditions, PDMS-LT exhibited a significant reduction in wear rate, measuring at 2.83 x 10-4 mm3/m.N, representing an impressive 80% enhancement over untreated surfaces. The corrosion resistance is notably improved with PDMS-LT surface exhibits a significantly reduced corrosion rate by 84% compared to UT surface. In conclusion, the results emphasize the potential of PDMS superhydrophobic fabrication combined with laser texturing to enhance the durability and performance of Ti6Al4V components across diverse industrial applications.